Expérimenter le maniement des armes à la fin du Moyen AgeExperimente zur Waffenhandhabung im Spätmittelalter - Jaquet, Daniel; Baptiste, Nicolas (Schwabe Verlag, 2019)
The volume presents interdisciplinary contributions that use practical experiments in order to examine historical european martial arts and the material culture of the arms of the late Middle Ages.